1995
DOI: 10.1103/physrevlett.75.4417
|View full text |Cite
|
Sign up to set email alerts
|

Improved Confinement with Reversed Magnetic Shear in TFTR

Abstract: Highly peaked density and pressure profiles in a new operating regime have been observed on the Tokamak Fusion Test Reactor (TFTR). The qprofile has a region of reversed magnetic shear extending from the magnetic axis to r / u-0.3-0.4. The central electron density rises from 0.45 x lo2' m-3 to nearly 1.2 x lo2' m-' during neutral beam injection. The electron particle diffusivity drops precipitously in the plasma core with the onset of the improved confinement mode and can be reduced by a factor of N 50 to near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
500
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 695 publications
(517 citation statements)
references
References 25 publications
13
500
0
Order By: Relevance
“…A number of facilities have recently added the capability to accuratelv measure the internal a Drofile evolution. and this has made possible systematic study of the production a n i performance of NCY regimes (Rice' 1996a(Rice' , 1996b(Rice' , 1996cLevinton 1995;Fujita 1997aFujita , 1997b.…”
Section: Negative Central Magnetic Shear (Ncs/lis/optimized Shear)mentioning
confidence: 99%
“…A number of facilities have recently added the capability to accuratelv measure the internal a Drofile evolution. and this has made possible systematic study of the production a n i performance of NCY regimes (Rice' 1996a(Rice' , 1996b(Rice' , 1996cLevinton 1995;Fujita 1997aFujita , 1997b.…”
Section: Negative Central Magnetic Shear (Ncs/lis/optimized Shear)mentioning
confidence: 99%
“…Therefore the slightly reduced set of equilibrium equations we will use in the following consists of Eqs. (2), (3), (4) for ions only, (5), (6), (7), (8), and (10). By expressing B θ in terms of the safety factor, q = rB θ /(R 0 B z ), with 2πR 0 associated with the length of the plasma column, and introducing the normalized radius ρ = r/r 0 with r 0 corresponding to the plasma surface, Eq.…”
Section: Two-fluid Cylindrical Equilibria With Reversed Magnetic Shearmentioning
confidence: 99%
“…(2)(3)(4)(5)(6)(7)(8) are advantageous in two respects: (i) the momentum equation includes the electric field and therefore the pressure gradient contribution to E can be calculated from this equation; this contribution is missing in the frame of MHD because E is calculated by Ohm's law, E + v × B = 0, and (ii) the current density J is related self-consistently to the fluid species velocities [Eq. (8)]. …”
Section: Two-fluid Cylindrical Equilibria With Reversed Magnetic Shearmentioning
confidence: 99%
See 1 more Smart Citation
“…Another situation in which the presence of magnetic field chaos can help plasma confinement is the creation of a transport barrier to reduce particle escape in tokamaks. It has been recently observed that this may occur if there is a negative magnetic shear region within the plasma column [5,6]. Such a region is created by means of a non-peaked plasma current density, corresponding to a non-monotonic radial profile for the safety factor [7].…”
Section: Introductionmentioning
confidence: 99%